The Economic Benefits of Integrating Sustainability to IT industry : Study of the impact of sustainability reporting to business incentives - Iivanainen, Arttu (My University, 2024)
As regulative environment in the field of sustainability is evolving and as the businesses need to address sustainability issues comprehensively in mandatory manner the need for adapting sustainability into to core of doing business grows. Sustainability reporting creates an incentive for improving business performance through considering sustainability impact thorough the whole business process and how it affects the stakeholders. IT sector plays a big role in the modern society and holds the capability to have a transforming positive impact in addressing sustainability issues from various sustainability dimensions. As companies subject to Corporate Sustainability Reporting Directive (CSRD) need to improve the sustainability performance and assess the risks and opportunities IT sector has a major business potential in helping other industries by creating more effective solutions and addressing extensive sustainability topics with more developed solutions and design. Sustainability reporting has been primarily under voluntary basis in the reporting and disclosure framework. The base of voluntary disclosure can be argued not to encourage companies to address the sustainability topics comprehensively hence it does not encourage the economy to make sustainability profitable. By voluntary disclosure companies can be considered to aim for better reputation and public image by positioning themselves as “sustainable” or “green” while the information disclosed is not regulated and thus not comparable and does not tell the whole story. Voluntary disclosure has not particularly improved the level of sustainability integration in the economy, but it provides a great way for companies to communicate the sustainability issues to external stakeholders and improve their credibility. Therefore, voluntary disclosure is argued to benefit the single companies more in short-term than the society and the impact of such dynamic is not sustainable anymore. As for regulative sustainability reporting the dynamic in the economy turns so integrating sustainability in the business becomes a business incentive. The mandatory nature of sustainability reporting creates a need for companies to innovate new ways of coming up with solutions and doing business. The regulation provides an equal framework to work in for all the actors in the market and encourages the businesses to innovate and develop their business to address sustainability topics comprehensively. The dynamic that sustainability reporting regulation brings to the economy and the market is creating business incentives from sustainability which benefits the whole society and builds the economy on a sustainable fashion. The regulative reporting is argued to benefit the whole society more due such dynamic. IT industry in this context is studied as it plays a big role in the economy and in the society. The sustainability dimensions provide a great framework to assess IT industry from as it has great impact especially on the triple bottom line: social, environmental, and economic dimensions. By addressing sustainability issues in design through every phase of solution development IT industry can impact positively to their clients, stakeholders and eventually to society by addressing sustainability in solution efficiency, user friendliness and inclusiveness. By doing so the industry answers the future challenges in sustainability and utilizes the opportunity in business provided by sustainability transition.

Kestävyyden raportoinnin regulaatio kehittyy jatkuvasti ja tarve sisällyttää kestävyysteemoja liiketoimintaan pakollisen raportoinnin ohjaamana kasvaa. Kestävyysraportointi luo yrityksille kannustimen parantaa ja kehittää toimintaa kestävyyden kautta ottaen huomioon se vaikutukset läpi liiketoimintaprosessien ja sen vaikutuksen sidosryhmille. IT sektorilla on valtava rooli nyky-yhteiskunnassa, sillä teknologisilla ratkaisuilla ja niiden kehittämisellä voidaan edistää kestävyyden positiivista vaikuttavuutta. EU:n kestävyysraportointidirektiivin CSRD:n (Corporate Sustainability Reporting Directive) tullessa voimaan, sen alaisten yritysten on raportoitava kestävyysvaikutuksistaan ja IT sektorilla on suuri liiketoiminnallinen mahdollisuus auttaa muiden alojen kehitystä tarjoamalla tehokkaampia ratkaisuja ja ottamalla huomioon laajasti kestävyysteemoja kehittyneille ratkaisuilla ja suunnittelulla. Kestävyysraportointi on pääsääntöisesti perustunut vapaaehtoiselle raportoinnille. Vapaaehtoiselle raportoinnille pohjautuvan järjestelmän voidaan ajatella olevan huono kannustamaan yrityksiä huomioimaan kestävyysteemoja kokonaisvaltaisesti, sillä järjestelmä ei tue kestävyyden kannattavuutta rahallisesti. Vapaaehtoisen raportoinnin avulla yritykset voivat luoda itselleen parempaa mainetta ja imagoa asemoimalla itseään kestäväksi toimijaksi. Samalla kuitenkaan raportteja ja julkaistua informaatiota ei ole reguloitu, joka tekee informaatiosta vertailukelvotonta sekä alttiin väärinkäytöksille. Vapaaehtoinen raportointi ei erityisesti ole parantanut kestävyyden integroimisen tasoa taloudessa, mutta se on loistava tapa yrityksille kommunikoida kestävyystoimistaan ulkoisille sidosryhmille ja parantaa julkisuuskuvaa. Näin ollen vapaaehtoisen raportoinnin voidaan ajatella hyödyttävän lähinnä yksittäisiä yrityksiä lyhyellä aikavälillä ja se vaikutuksen yhteiskunnalle olevan resursseja kuluttava. Puolestaan reguloitu kestävyysraportointi kääntää dynamiikan niin, että kestävyyden integroimisesta tulee liiketoiminnallinen ajuri. Kestävyysraportoinnin pakollisuus luo yrityksille tarpeen innovoida uusia ratkaisuja ja tapoja edistää liiketoimintaa. Regulaatio tarjoaa markkinoilla kaikille yrityksille tasa-arvoisen viitekehyksen ja kannustaa innovoimaan sekä kehittämään toimintaa kokonaisvaltaisemmin kestäväksi. Kestävyysraportoinnin regulaatio luo markkinoille liiketoiminnallisia kannustimia kestävyydestä, mikä hyödyttää koko yhteiskuntaa sekä kehittää taloutta kestävällä tavalla, joten regulatiivisen raportoinnin voidaan ajatella hyödyttävän kokonaisvaltaisesti koko yhteiskuntaa. Kestävyyden ulottuvuudet tarjoavat kattavan viitekehyksen arvioida IT teollisuuden vaikuttavuutta eritoten sosiaalisen, ympäristöllisen sekä taloudellisen ulottuvuuksien kautta. IT teollisuudella on laaja vaikutus yhteiskuntaan sekä talouteen, joten sen rooli on erittäin tärkeä kestävän kehityksen edistämisessä. Huomioimalla kestävyysteemoja suunnittelun sekä designin kautta ratkaisujen kehittämisen joka vaiheessa, voi IT teollisuus vaikuttaa positiivisesti asiakkaihin, sidosryhmiin ja yhteiskuntaan ratkaisujen tehokkuuden, käyttäjäystävällisyyden sekä osallistavuuden kautta. Ottamalla kestävyysteemat huomioon liiketoiminnassaan IT yritykset kykenevät varautumaan kestävyysteemojen tuomiin haasteisiin sekä hyödyntämään liiketoimintamahdollisuuksia, jotka syntyvät kestävyyssiirtymän myötä.
Keywords: Regulation, Reporting, Sustainability, IT industry, regulaatio, raportointi, kestävyys, IT teollisuus